(untitled) (Journal of Applied Business and Economics, 2024)
We make seven direct intra-brand comparisons between legacy carmakers’ electric vehicle (EV) and gas-powered vehicle who achieved top ten most-efficient electric vehicles in America. We find six out of the seven EVs will be able to breakeven the higher price relative to their gas counterparts within reasonable gas price range, electricity charge range, and federal government tax credit for buying EVs. We further find that federal government tax credit is the most effective policy tool that will induce new car buyers to choose EVs over comparable same-brand gas vehicle though other green initiatives such as solar panels on owner’s roof tops and below-market-interest-rate (BMIR) loans are effective as well.